Road wanderers in Brazil: a study on modern psychosocial human mobility - Justo, José Sterza [UNESP]; Nascimento, Eurípedes Costa do [UNESP] (Academic Journals, 2012)
Human mobility patterns are quite diverse nowadays and a very singular, extreme pattern is seen in the Brazilian scene: road wandering. Road wanderers are individuals who leave their home, family, work and other territories of a settled life and throw themselves into a life of solitary wandering along Brazilian highways. This study aimed to describe the lifestyle of road wanderers, investigate the reasons that led them choose this way of living and understand it against a background of modern human mobility patterns. A total of 63 interviews were conducted with individuals wandering on road shoulders. We found road wandering is associated with the following determinants: poverty; unemployment; marital conflicts; emotional suffering following the loss of loved ones; desires for adventure and freedom; and cultural symbols related to journey, migration, exodus and other modes of displacement. Despite its particularities, road wandering can be understood as a way of human mobility in the modern world.
Keywords: Wandering; Road wanderer; Mobility; Migration